A metal-free synthetic approach to peptide-based iminosugar clusters as novel multivalent glycosidase inhibitors. Issue 3 (4th January 2016) - Zelli, Renaud; Bartolami, Eline; Longevial, Jean-François; Bessin, Yannick; Dumy, Pascal; Marra, Alberto; Ulrich, Sébastien
Abstract : Oxime ligation allowed the preparation of a set of iminosugar clusters from which new Jack bean α-mannosidase inhibitors were identified. Abstract : Multivalent bioconjugates represent emerging tools for enzyme inhibition. In particular, iminosugar clusters have recently shown promising results for the inhibition of glycosidases. However, most of them are prepared by copper-mediated click reactions. We report herein a metal-free approach based on oxime ligation for preparing iminosugar clusters using cyclic and linear tetra-aldehyde peptide scaffolds and oxyamine iminosugars (40–70% yield). Glycosidase inhibition assays revealed the superiority of the clusters made of the linear scaffold, displaying up to a 77-fold increase of relative potency per iminosugar. Thus, this metal-free approach provides a rapid access to structurally-diverse iminosugar clusters for establishing structure–activity relationships in the context of multivalent glycosidase inhibition.